2015
DOI: 10.1007/s00018-015-2009-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of olfactory receptor family reveal unusual characteristics of the olfactory system in the migratory locust

Abstract: Locusts represent the excellent model of insect olfaction because the animals are equipped with an unusual olfactory system and display remarkable density-dependent olfactory plasticity. However, information regarding receptor molecules involved in the olfactory perception of locusts is very limited. On the basis of genome sequence and antennal transcriptome of the migratory locust, we conduct the identification and functional analysis of two olfactory receptor families: odorant receptors (ORs) and ionotropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
82
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 59 publications
4
82
1
Order By: Relevance
“…Moreover, 4 PameORs ( 17, 74, 75 , and 81 ) and 4 PameIRs ( 21, 31, 35 and 42 , and six iGluRs ( iGluR1–6 ) exhibited non-chemosensory organ-biased expression. All of them expressed in the legs to a certain extent, which was consistent with some previous studies364748. However, we could not ignore their olfactory function; as reported earlier, IR expression in the legs affected the mating behaviour of fly47.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, 4 PameORs ( 17, 74, 75 , and 81 ) and 4 PameIRs ( 21, 31, 35 and 42 , and six iGluRs ( iGluR1–6 ) exhibited non-chemosensory organ-biased expression. All of them expressed in the legs to a certain extent, which was consistent with some previous studies364748. However, we could not ignore their olfactory function; as reported earlier, IR expression in the legs affected the mating behaviour of fly47.…”
Section: Discussionsupporting
confidence: 89%
“…The number of ORs was much higher than in the two other Blattaria species, Z. nevadensis (60 ORs, genome data)31 and B. germanica (5 ORs, antennal transcriptome data)30. It was also higher than the 62 ORs found in D. melanogaster 15 and the 79 ORs in A. gambiae 635, but was much lower than the number of ORs reported in T. castaneum (259 ORs)8, A. mellifera (170 ORs)7, and L. moratoria (142 ORs)36. The number of IRs was lower than the numbers found in Z. nevadensis (136 IRs)31 and higher than those found in B. germanica (5 IRs, antennal transcriptome data)30, but it was much higher than the 14 IRs found in A. gossypii 24 and Sogatella furcifera 23, 57 in D. melanogaster 202237, and 22 in A. gambiae 38.…”
Section: Discussionmentioning
confidence: 79%
“…The expression of broadly expressed OR genes in non-olfactory tissues suggested that they might have diverse physiological functions in other organs. The co-expression of LmigOR95 and LmigOrco were also observed in the fat body of migratory locust37. In locusts and mosquitoes, the testis-enhanced OR genes supposed to participate in the sperm chemotaxis, fertilization, or the activation of spermatozoa3745.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, because the ORF of some ORs is incomplete, we cannot exclude the possibility that some of these ORs might be pseudogenes. The sequence number is much lower compared with species including Apis mellifera (163 ORs)35, Tribolium castaneum (341ORs)36, and Locusta migratoria (142 ORs)37. This may be caused by adaptation of distinct species to their hosts during evolution38.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation